How to sell renewable electricity: Interactions of the intraday and day-ahead market under uncertainty - Andreas Knaut; Frank Obermüller (Institute of Energy Economics at the University of Cologne (EWI), 2016)
Uncertainty about renewable production increases the importance of sequential short-term trading. We consider a two-stage market where conventional and renewable producers compete in order to satisfy the demand of consumers. The trading in the first stage takes place under uncertainty about production levels of renewable producers, which can be associated with trading in the day-ahead market. In the second stage, which we consider as the intraday market, uncertainty about the production levels is resolved. Our model is able to capture different levels of flexibility for conventional producers as well as different levels of competition for renewable producers. We find that it is optimal for renewable producers to sell less than the expected production in the day-ahead market. In situations with high renewable production it is even profitable for renewable producers to withhold quantities in the intraday market. However, for an increasing number of renewable producers, the optimal quantity tends towards the expected production level. More competition as well as a more flexible power plant fleet lead to an increase in overall welfare, which can even be further increased by delaying the gate-closure of the day-ahead market or by improving the quality of renewable production forecasts.
Keywords: D81; L13; L94; Q21; 330; Cournot Competition; Electricity Markets; Day-ahead Market; Intraday Market; Competition Under Uncertainty